Force patterning drives quasistratification and graded tissue-scale spatial order in auditory epithelia - Julian Weninger; Anubhav Prakash; Sukanya Raman; Raj K. Ladher; Madan Rao; Karsten Kruse (Proceedings of the National Academy of Sciences, 2026)
During development, coordinated cell behaviors drive epithelial morphogenesis toward precise three-dimensional architectures essential for physiological function. How such coordination arises in epithelia composed of multiple cell types remains unclear. Here, we study development of the avian auditory epithelium comprising sensory hair cells (HCs) and nonsensory supporting cells (SCs). Initially, HCs and SCs are arranged into mosaics by Notch–Delta signaling. As development proceeds, HCs partially extrude from the epithelium, establish a tenfold gradient in apical surface area across the tissue, and rearrange with SCs to form near-hexagonal order. Using experiments combined with a three-dimensional vertex model, we show that increased contractility at apical junctions between SCs relative to HC–SC junctions drives spatial organization both within the epithelial plane and along the apical–basal axis. Consistent with experimental findings, our simulation shows systematic differences in HC apical area expansion generate opposing coordinated movements of HCs and SCs, establishing gradients in HC apical surface area and density while maintaining uniform hexagonal order. Together, these results demonstrate that spatial patterning of junctional contractility coordinates cell behavior across both the plane and depth of a mixed epithelium, producing quasi-stratified architecture and tissue-scale three-dimensional order.